Actin binding proteins in blood–testis barrier function. Issue 3 (June 2015) - Li, Nan; Mruk, Dolores D.; Cheng, C. Yan
Abstract : Purpose of review: The present review examines the role of actin binding proteins (ABPs) on blood–testis barrier (BTB), an androgen-dependent ultrastructure in the testis, in particular their involvement on BTB remodeling during spermatogenesis. Recent findings: The BTB divides the seminiferous epithelium into the basal and the adluminal compartments. The BTB is constituted by coexisting actin-based tight junction, basal ectoplasmic specialization, and gap junction, and also intermediate filament-based desmosome between Sertoli cells near the basement membrane. Junctions at the BTB undergo continuous remodeling to facilitate the transport of preleptotene spermatocytes residing in the basal compartment across the immunological barrier during spermatogenesis. Thus, meiosis I/II and postmeiotic spermatid development take place in the adluminal compartment behind the BTB. BTB remodeling also regulates exchanges of biomolecules between the two compartments. As tight junction, basal ectoplasmic specialization, and gap junction use F-actin for attachment, actin microfilaments rapidly convert between their bundled and unbundled/branched configuration to confer BTB plasticity. The events of actin reorganization are regulated by two major classes of ABPs that convert actin microfilaments between their bundled and branched/unbundled configuration. Summary: We provide a model on how ABPs regulate BTB remodeling, shedding new light on unexplained male infertility, such as environmental toxicant-induced reproductive dysfunction since the testis, in particular the BTB, is sensitive to environmental toxicants, such as cadmium, bisphenol A, phthalates, and PFOS (perfluorooctanesulfonic acid or perfluorooctane sulfonate).